Climate Change Finance in Nepal: A Review from Policy Framework and Practice - Rawal, Shital Bahadur (Journal of Sustainability and Environmental Management, 2024)
This study deals with climate change finance and its policy frameworks in Nepal. Primarily, this study aims to examine how the government of Nepal has been spending public funds on climate-related projects and activities, and what types of policy initiatives have been taken to respond to the climate change impact as a party of UNFCCC. Secondly, this paper aims to recommend necessary reform in existing policy and practice by reviewing the policy framework and other legal arrangements for climate change in Nepal. This study has been conducted based on the desk review methodology (desk survey method) which is mainly based on the data and information available from the public finance management system of Nepal. The finding of this study reveals that the government of Nepal allocates about 32.5% of the total national budget annually to highly and moderately relevant climate change activities. In terms of public spending on climate change, the total climate change expenditure has been increasing over the last three years, and out of total climate-related expenditure, there is a higher share of local government which is 47%. In contrast, the share of the federal government is 36% and the provincial government is 17% respectively. This study shows that the major portion of climate change finance has been invested from the source of the Nepal government which is 89% of total climate finance whereas foreign aid contributes 9% and kinds and direct payment contribute 2% of the total climate expenditure respectively. As per the Development Cooperation Report 2022, among all the 361 projects under implementation through official development assistance (ODA), out of which, 35 projects are highly relevant to climate change, for which USD 53 million has been disbursed, 76 projects are moderately relevant to climate change for which USD 379 million has been disbursed and 250 projects are neutral for which USD 988 million has been disbursed in 2022.